1997
DOI: 10.1091/mbc.8.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Fast receptor-induced formation of glycerophosphoinositol-4-phosphate, a putative novel intracellular messenger in the Ras pathway.

Abstract: Glycerophosphoinositols are phosphoinositide metabolites whose levels are constitutively elevated in Ras-transformed cells. Here, we show that one of these compounds, glycerophosphoinositol-4-phosphate (GroPlns-4-P) responds acutely to the stimulation of the epidermal growth factor receptor, with a fast, massive and transient increase. The mechanism leading to GroPIns-4-P formation involves the activation of phosphoinositide-3 kinase and the small GTP-binding protein Rac, since GroPIns-4-P was neither formed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…Notably, Table 2 suggests that not all of the increase of Ins-1-P and Ins-2-P can be explained as derived from Ins-1 : 2-cycP since these two metabolites remained elevated in Ras-transformed ®broblasts even after neutral extraction (four-and 40-fold higher, respectively). Indeed, it is possible that these metabolites derive from GroPIns via enzymatic hydrolysis, as previously suggested Falasca et al, 1996Falasca et al, , 1997. In contrast, inositol phosphates produced by phospholipase C activation such as Ins-1,4-P 2 and Ins-1,4,5-P 3 , in agreement with previous studies, were not signi®cantly higher in Rastransformed than in normal cells (Table 1) (Alonso et al, 1988;Valitutti et al, 1991;Iacovelli et al, 1993;Corda and Falasca, 1996;Falasca and Corda, 1994).…”
Section: Phosphoinositide Metabolism In Frt-fibro and Frt-fibro Ha-ramentioning
confidence: 78%
See 2 more Smart Citations
“…Notably, Table 2 suggests that not all of the increase of Ins-1-P and Ins-2-P can be explained as derived from Ins-1 : 2-cycP since these two metabolites remained elevated in Ras-transformed ®broblasts even after neutral extraction (four-and 40-fold higher, respectively). Indeed, it is possible that these metabolites derive from GroPIns via enzymatic hydrolysis, as previously suggested Falasca et al, 1996Falasca et al, , 1997. In contrast, inositol phosphates produced by phospholipase C activation such as Ins-1,4-P 2 and Ins-1,4,5-P 3 , in agreement with previous studies, were not signi®cantly higher in Rastransformed than in normal cells (Table 1) (Alonso et al, 1988;Valitutti et al, 1991;Iacovelli et al, 1993;Corda and Falasca, 1996;Falasca and Corda, 1994).…”
Section: Phosphoinositide Metabolism In Frt-fibro and Frt-fibro Ha-ramentioning
confidence: 78%
“…However, also LysoPtdIns and glycerophosphoinositol-4-phosphate (GroPlns-4-P) possess biological activity (Iacovelli et al, 1993;Falasca and Corda, 1994;Corda and Falasca, 1996). Exogenously added GroPlns-4-P inhibits adenylyl cyclase, probably by acting at the level of the Gs protein (Iacovelli et al, 1993), and a similar eect is observed when GroPlns-4-P is formed intracellularly by growth factor receptor activation (Falasca et al, 1997). More important in the context of the Ras-induced transformation, exogenously added LysoPtdIns stimulates cell proliferation in Rastransformed thyroid cells via the activation of phospholipases C and A 2 (Falasca and Corda, 1994;Falasca et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, increases in cAMP levels result in the inhibition of RhoA, with respect to its ability to induce either morphological changes in neuroblastoma cells or cell migration in colon carcinoma and hepatoma cells (Dong et al, 1998;Mukai et al, 2000;O'Connor et al, 2000). Thus, a decrease in cAMP induced in Swiss 3T3 cells by GroPIns-4P (Falasca et al, 1997) might play at least an accessory role in Rac and Rho activation also in fibroblasts. Irrespective of the precise manner in which Rac is activated, an intriguing and potentially important mechanistic aspect emerges from the comparison between the stimulatory effects of GroPIns-4P and those of the other glycerophosphoinositols.…”
Section: Effect Of Gropins-4p On Rac: Requirement For a Long-lasting mentioning
confidence: 99%
“…First, they define a new biological activity of an endogenous, freely diffusable inositol-containing molecule. Moreover, because GroPIns-4P is a natural metabolite of the phosphoinositides generated by the activation of the Ras cascade (Falasca et al, 1995(Falasca et al, , 1997, the actin remodeling it induces is likely to play a role in motility and metastatic invasion. Second, because GroPIns-4P is a small, water-soluble molecule that is active when added extracellularly, our observations suggest that it has the potential to serve as a prototype of a new class of pharmacologically active agents.…”
Section: Introductionmentioning
confidence: 99%